Prevalence and Antimicrobial Profile of Blood Infections from Clinical Isolates at Tertiary Care Hospital of North India - Ruchika, Dr; Dr. Rupinder Bakshi; Dr. Jaspreet Kaur Boparai; Dr. Lavisha; Dr. KarashdeepKaur; Dr. Satinder Kaur; Dr. Arunita Ghosal; Dr. Palika Sharma (GMC Patiala Journal of Research and Medical Education, 2023)
ABSTRACT: Background: Arboviruses of public health importance, such as dengue and chikungunya, have caused several epidemics in many tropical and subtropical countries. The clinical manifestations, vector, and pathogenic processes of the dengue and chikungunya viruses are identical. Aims and objectives: The present study is to study the prevalence of Dengue and Chikungunya co-infection in tertiary care hospital. Material and Methods: Serum samples were received from RH Patiala and processed in VRDL, Government Medical College, Patiala, between January 2022 to November 2022. The samples were processed depending upon the H/O duration of the fever in days. For fever less than 4 days Dengue NS1Ag detection kits was used and for fever >4 days DENV IgM antibody capture (MAC) ELISA and CHIK IgM ELISA kits were used. The testing was done by using kit protocol. The serotyping was done by using Real time RT PCR kit received from NIV Pune as per kit protocol. Results: Out of total 2188 samples from suspected patients for dengue infection, 546 samples were positive for DENV while CHIK IgM antibodies were positive in 47 patients out of the total suspected 102 cases and co infection was seen in 2 cases. The results of 43 serotyping revealed that DENV 2 is more common followed by DENV 1 and DENV 3, while no case of DENV 4 serotype was detected. Out of 546 Dengue virus positive cases 321 were male patients and 225 were female patients, whereas, CHIKV positive cases was reported in 21 male and 26 female patients. However, co-infection of DENV and CHIKV was reported in one male and one female patient. Conclusion: Dengue and Chikungunya coinfection as a global problem worthy of consideration. It is therefore pertinent that both infections be assessed during diagnosis, mosquito vector control practices be implemented, and vaccine development strides be supported globally. Keywords: Dengue, Chikungunya, Coinfection